2012
DOI: 10.2147/cer.s33447
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness trial of family-supported smoking cessation intervention versus standard telephone counseling for chronically ill veterans using proactive recruitment

Abstract: Objectives:Smoking cessation among patients with chronic medical illnesses substantially decreases morbidity and mortality. Chronically ill veteran smokers may benefit from interventions that assist them in harnessing social support from family and friends. Methods: We proactively recruited veteran smokers who had cancer, cardiovascular disease, or other chronic illnesses (diabetes, chronic obstructive pulmonary disease, hypertension) and randomized them to either standard telephone counseling or family-suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…While the evidence for the efficacy of NRT in clinical trials is convincing (Stead et al, 2012), there is growing controversy and concern over the effectiveness of NRT in real world settings. Several recent studies have shown little to no benefit for NRT in the context of effectiveness trials or real world settings (Alpert et al, 2012; Bastian et al,2012; Kotz et al, 2013; Kotz et al, 2014). A recent large, population-based effectiveness study (Cunningham et al, 2016) that examined the effectiveness of simply mailing NRT to smokers found that NRT was associated with significantly higher cessation rates; 7.4% of smokers mailed NRT (without behavioral support) reported abstinence compared to 3% in a control group that received no NRT (bio-verified results suggest 2.8% of smokers in the NRT intervention were abstinent vs. 1% in the control group).…”
Section: 0 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the evidence for the efficacy of NRT in clinical trials is convincing (Stead et al, 2012), there is growing controversy and concern over the effectiveness of NRT in real world settings. Several recent studies have shown little to no benefit for NRT in the context of effectiveness trials or real world settings (Alpert et al, 2012; Bastian et al,2012; Kotz et al, 2013; Kotz et al, 2014). A recent large, population-based effectiveness study (Cunningham et al, 2016) that examined the effectiveness of simply mailing NRT to smokers found that NRT was associated with significantly higher cessation rates; 7.4% of smokers mailed NRT (without behavioral support) reported abstinence compared to 3% in a control group that received no NRT (bio-verified results suggest 2.8% of smokers in the NRT intervention were abstinent vs. 1% in the control group).…”
Section: 0 Discussionmentioning
confidence: 99%
“…Interested participants received a tailored dose of NRT and delivery type based on number of cigarettes smoked per day using an established protocol (e.g., Bastian et al, 2012). This could include an 8-week course of nicotine patches and up to two rescue methods (e.g., nicotine lozenge, gum).…”
Section: Methodsmentioning
confidence: 99%
“…All participants received up to five telephone counseling sessions over a four-month intervention period. 22 Each counseling session included standard content related to smoking cessation (e.g., getting ready for your quit date, how to handle slips) tailored to each participant's needs. The main distinction between the two arms of this comparative effectiveness study was that the family supported intervention was designed to increase positive interactions between the participant and their designated support person to facilitate smoking cessation.…”
Section: Methodsmentioning
confidence: 99%
“…At five-month follow-up, we found no differences in seven-day point prevalence smoking cessation by arm: 19.8% in the family supported intervention and 22.0% in the standard arm. 22…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation